miRNA-Mediated Control of B Cell Responses in Immunity and SLE - Schell, Stephanie L.; Rahman, Ziaur S. M. (Frontiers in Immunology, 2021)
Loss of B cell tolerance is central to autoimmune diseases such as systemic lupus erythematosus (SLE). As such, the mechanisms involved in B cell development, maturation, activation, and function that are aberrantly regulated in SLE are of interest in the design of targeted therapeutics. While many factors are involved in the generation and regulation of B cell responses, miRNAs have emerged as critical regulators of these responses within the last decade. To date, miRNA involvement in B cell responses has largely been studied in non-autoimmune, immunization-based systems. However, miRNA profiles have also been strongly associated with SLE in human patients and these molecules have proven critical in both the promotion and regulation of disease in mouse models and in the formation of autoreactive B cell responses. Functionally, miRNAs are small non-coding RNAs that bind to complementary sequences located in target mRNA transcripts to mediate transcript degradation or translational repression, invoking a post-transcriptional level of genetic regulation. Due to their capacity to target a diverse range of transcripts and pathways in different immune cell types and throughout the various stages of development and response, targeting miRNAs is an interesting potential therapeutic avenue. Herein, we focus on what is currently known about miRNA function in both normal and SLE B cell responses, primarily highlighting miRNAs with confirmed functions in mouse models. We also discuss areas that should be addressed in future studies and whether the development of miRNA-centric therapeutics may be a viable alternative for the treatment of SLE.